In Vivo Mouse Pathogenicity Study of E.Coli Isolated from Porcine Gastrointestinal Tract - Sithara, M.S.; George, Ajith Jacob; Vijayan, N.; Manomohan, C.B.; Mani, Binu K. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was carried out to assess the degree of pathogenicity of E.coli, isolated from the GI tract of piglets . All the mice inoculated with E.coli isolates died within 36 hours. Post-mortem examination of the mice revealed lesions similar to that observed in most of the natural infection cases in piglets. The E.coli were re-isolated from the dead mice by streaking on EMB agar. Thus in the present study E.coli isolated from the GI tract of piglets was found to be highly pathogenic to mice and was also re-isolated from the dead mice indicating that E.coli could be responsible for mortality in piglets.